Measures of trait mindfulness: Convergent validity, shared dimensionality, and linkages to the five-factor model - Siegling, A. B.; Petrides, K. V. (Frontiers in Psychology, 2014)
This study investigated, and partially aimed to replicate, important construct validity aspects and the homogeneity of trait mindfulness measures. Specifically, the study set out to examine whether a single dimension can explain the shared variance among these measures as well as the extent to which they converge with one another and in terms of their linkages to the Five-Factor Model (FFM). Two samples completed all trait measures of the construct and one of them additionally completed a measure of the Big Five personality traits. Results showed that a single dimension explains the shared variance among measures based on the original, Eastern conceptualization of mindfulness, although not all of them seem to represent this construct comprehensively. Intercorrelations, dimensionality analysis, as well as linkages to the FFM indicated that the Eastern and Western conceptualizations, and their respective measures, reflect distinct constructs. However, the amount of variance overlap with the FFM was similar across the two conceptualizations.